LECTURER IN UNDERSTANDING THE INFLUENCE OF QUALITY AND INTEREST IN SELECTING STUDENTS MAJORS - Sulistiyani Sulistiyani; Sugeng Samiyono (Fakultas Ekonomi Universitas Negeri Jakarta, 2020)
Abstract This study aims to determine the relationship of lecturers in the understanding and interest of students in the selection of majors. This study to find out how big the role of lecturers in increased understanding and interest of students in the selection of majors. This study was conducted using a probability sampling type of simple random sampling with a sample of 100 respondents from accounting students with a concentration of taxation. The data used are primary data through questionnaires. In this study using the test models as well as the MRA test. These results indicate that the quality of lecturers affects the understanding of accounting and taxation understanding. Faculty quality, understanding of accounting and taxation understanding significantly influence the electoral interest of majors. Keywords: Lecturers quality, understanding and interest Students on Election Majors